1974
DOI: 10.1111/j.1365-2621.1974.tb17974.x
|View full text |Cite
|
Sign up to set email alerts
|

Pentane Formation and Rancidity in Vegetable Oils and in Potato Chips

Abstract: S Pentane formation during initial stages of autoxidation is indicative of rancidity in aged vegetable oils and potato chips. Pentane in the headspace gas of oils and chips was measured by gas chromatography. An 18‐member taste panel evaluated the samples for development of rancid odors and flavors. Significant linear correlations were obtained between the amount of pentane developed and the number of rancid descriptions. Samples needed only 0.08 ppm pentane in the headspace to be described as rancid by 90% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1978
1978
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Pen-tane evolved from peroxides during their decomposition has been corre lated with rancidity [34,35], and studies of pentane formation in foods have shown that it is possible to correlate linoleate content and iodine values with the induction period for pentane formation [36]. Pen-tane evolved from peroxides during their decomposition has been corre lated with rancidity [34,35], and studies of pentane formation in foods have shown that it is possible to correlate linoleate content and iodine values with the induction period for pentane formation [36].…”
Section: Pentane In Breath As a Measure Of In Vivo Lipid Peroxidmentioning
confidence: 99%
“…Pen-tane evolved from peroxides during their decomposition has been corre lated with rancidity [34,35], and studies of pentane formation in foods have shown that it is possible to correlate linoleate content and iodine values with the induction period for pentane formation [36]. Pen-tane evolved from peroxides during their decomposition has been corre lated with rancidity [34,35], and studies of pentane formation in foods have shown that it is possible to correlate linoleate content and iodine values with the induction period for pentane formation [36].…”
Section: Pentane In Breath As a Measure Of In Vivo Lipid Peroxidmentioning
confidence: 99%
“…Good correlation is, for example, reported between rancid odor and concentration of hexanal in explosion-puffed potatoes (Konstance et al 1978) as well as in other low fat, dehydrated foods (Fritsch and Gale 1977). In vegetable oils and in potato chips, significant correlations between the amount of pentane detected in headspace and the rancidity described by a trained panel is reported (Warner et al 1974). The concentration of pentane has also been found to correlate with taste panel scores for nutcontaining products (Bigalli 1977).…”
Section: Introductionmentioning
confidence: 96%
“…Fried-food flavor may be partly derived from the formation of 2,4-decadienal during the thermal oxidation of linoleic acid (11,12). Potato chips fried in oils with a range of linoleic acid from 17 to 78% showed a correlation coefficient of 0.87 (P < 0.05) between increasing linoleic acid and decreasing oxidative stability (13). Both the fried-food flavor intensity of the fried food and the length of the frying life of the oil must be optimized by selecting appropriate fatty acid compositions for frying oils.…”
mentioning
confidence: 97%